Reinforced concrete building design project & project based learning (Case Study) - Azahari, Nur Balqis Qurratu'ain (2022)
Civil engineering programs rely on Standards and Codes of Practice to help them through the process of fulfilling their design and workmanship responsibilities. Essentially, standards or practice standards serve as a formalised representation of the accumulated knowledge and technical competence that has accrued over time in the building and construction business. We must have a thorough understanding of concrete in order to construct reinforced concrete that is not as simple as we had anticipated. As we all know, concrete is the most often used building material, second only to steel. As a result, it is critical to design reinforced concrete in accordance with the Code of Practice. In addition, al 1 construction purposes must adhere to the Malaysian Standard Eurocode Code of Practice, which is available online. In addition, we must abide by the Uniform Building By Law, which is a federal statute. If we did not adhere to the legislation, our project could be negatively impacted in terms of cost, timeliness, and other factors. Furthermore, designing reinforced concrete is critical since we want to produce a structure that will be used by the customer. To put it another way, we as designers must create carefully in order to avoid causing damage or accident to the customer. As civil engineers, it is our responsibility to design all elements in such a way that they can survive any dangerous situation, such as an earthquake, flash f1ood, severe wind, and so on. Each element of the building must be manually calculated, including the slab, beam, column, pad footing, and staircase. Each section's calculations must be submitted to the lecturer. In other words, they cannot go to the column if they fail to calculate the beam manually. Students have a lot of time during class to refer to their calculations, thus all efforts are on the students. Students must use reputable manuals, codes, standards, and data publications to gather data. Then use the formula to calculate the size of steel bars, bearing wall thickness, concrete, etc. Manual has the issue that various experts may come to different conclusions For diploma level, we only need to design static buildings in which the wind motion is not taken into consideration throughout the design process. Because of this, we need to have a fundamental understanding of the subject as civil engineering students. The use of an uniform Code of Practice will ensure that all aspects of the construction are standardised